Hearing Kyriotic sonship : a cognitive and rhetorical approach to the characterization of Mark's Jesus - Whitenton, Michael R. (Biblical Interpretation Series, 2016)
In Hearing Kyriotic Sonship Michael Whitenton explores first-century audience impressions of Mark's Jesus in light of ancient rhetoric and modern cognitive science. Commonly understood as neither divine nor Davidic, Mark's Jesus appears here as the functional equivalent to both Israel's god and her Davidic king. The dynamics of ancient performance and the implicit rhetoric of the narrative combine to subtly alter listeners' perspectives of Jesus. Previous approaches have routinely viewed Mark's Jesus as neither divine nor Davidic largely on the basis of a lack of explicit affirmations. Drawing our attention to the mechanics of inference generation and narrative persuasion, Whitenton shows us that ancient listeners probably inferred much about Mark's Jesus that is not made explicit in the narrative.